2013
DOI: 10.1080/0145935x.2013.859906
|View full text |Cite
|
Sign up to set email alerts
|

Trust-Based Relational Intervention (TBRI): A Systemic Approach to Complex Developmental Trauma

Abstract: Children and youth who have experienced foster care or orphanage-rearing have often experienced complex developmental trauma, demonstrating an interactive set of psychological and behavioral issues. Trust-Based Relational Intervention (TBRI) is a therapeutic model that trains caregivers to provide effective support and treatment for at-risk children. TBRI has been applied in orphanages, courts, residential treatment facilities, group homes, foster and adoptive homes, churches, and schools. It has been used eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(46 citation statements)
references
References 94 publications
0
46
0
Order By: Relevance
“…Future research should invariably include a focus on identifying viable options and avenues for facilitating trust among those affected by combat-related PTSD symptomatology. At present, (re)establishing the capacity to trust is described as a secondary outcome of existing PTSD treatment options, with cognitive behavioral therapy being the most promising treatment for facilitating general trust ( 58 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…Future research should invariably include a focus on identifying viable options and avenues for facilitating trust among those affected by combat-related PTSD symptomatology. At present, (re)establishing the capacity to trust is described as a secondary outcome of existing PTSD treatment options, with cognitive behavioral therapy being the most promising treatment for facilitating general trust ( 58 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Correcting Principles are used to deliberately shape behavior, but will only be effective to the extent that their practice is based on a firm foundation of Empowering and Connecting. A more detailed explanation of TBRI and how the principles are applied can be found in previous publications (e.g., Purvis et al 2013a , b ).…”
Section: Trust-based Relational Intervention As Trauma-informed Carementioning
confidence: 99%
“…Developed at the Institute of Child Development at Texas Christian University, TBRI has been used successfully with families, group homes, summer camps, and school environments. Other publications describe the components of TBRI in more detail (Purvis et al 2013a(Purvis et al , 2011(Purvis et al , 2007b(Purvis et al , 2009, empirical evidence supporting TBRI (Purvis and Cross 2007;Purvis et al 2007aPurvis et al , b, 2012, and implementation in a public school setting (Parris et al 2014). In one study (Purvis et al 2007a), children who attended a TBRI summer camp demonstrated significant decreases in thought problems, attention problems, aggressive behavior, depressive symptoms, negative mood, and salivary cortisol levels (indicating reduced stress and anxiety) as well as improvements in attachment behaviors and interpersonal relationships.…”
Section: Trust-based Relational Interventionmentioning
confidence: 99%